Patient Experiences in Managing Chronic Illness After the 2023 Kahramanmaraş Earthquake in Türkiye: A Qualitative Study - Tuluce, Derya; Turan, Zeliha; Akcan, Kubra; Bektas, Oktay (Wiley, 2025)
The primary purpose of this study is to determine the experiences of individuals with chronic illnesses related to managing their illnesses after the February 6, 2023, Kahramanmara & scedil; earthquake in T & uuml;rkiye. This study was conducted using phenomenological methodology. The study employed purposeful and criterion sampling, and 12 participants were included. Data were collected using an in-depth interview technique and a semi-structured interview form. The data obtained showed that the central theme of the study was the earthquake process and that the data was analyzed in three categories: factors affecting illness management, changes in health status, and methods of coping with problems. Various problems are experienced regarding managing chronic illnesses in the post-earthquake period. These problems leave short- or long-term adverse effects on the individual or social level.
Keywords: chronic illness; earthquake; illness management; nursing care; qualitative study